2015
DOI: 10.1038/srep08082
|View full text |Cite
|
Sign up to set email alerts
|

The relevance of nanoscale biological fragments for ice nucleation in clouds

Abstract: Most studies of the role of biological entities as atmospheric ice-nucleating particles have focused on relatively rare supermicron particles such as bacterial cells, fungal spores and pollen grains. However, it is not clear that there are sufficient numbers of these particles in the atmosphere to strongly influence clouds. Here we show that the ice-nucleating activity of a fungus from the ubiquitous genus Fusarium is related to the presence of nanometre-scale particles which are far more numerous, and therefo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
275
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(293 citation statements)
references
References 47 publications
17
275
0
1
Order By: Relevance
“…In this figure the blanks refer to the freezing properties of the sample after 0.02 µm filtration. The blanks may still contain some INPs since some particles < 0.02 µm in diameter can act as INPs (Dreischmeier et al, 2017;O'Sullivan et al, 2015). The freezing properties of the blanks (after correction for freezing point depression by the salts) are similar to or lower than the freezing properties of ultrapure water, which are also shown in Fig.…”
Section: Inps In the Microlayer And Bulk Seawatermentioning
confidence: 56%
See 1 more Smart Citation
“…In this figure the blanks refer to the freezing properties of the sample after 0.02 µm filtration. The blanks may still contain some INPs since some particles < 0.02 µm in diameter can act as INPs (Dreischmeier et al, 2017;O'Sullivan et al, 2015). The freezing properties of the blanks (after correction for freezing point depression by the salts) are similar to or lower than the freezing properties of ultrapure water, which are also shown in Fig.…”
Section: Inps In the Microlayer And Bulk Seawatermentioning
confidence: 56%
“…Between 15 to 20 droplets of the sample, with volumes of 0.6 µL each, were deposited onto a hydrophobic glass slide (HR3-215; Hampton Research, Aliso Viejo, CA, USA) using a pipette. The slides were put into an airtight cell (Parsons et al, 2004) attached to a cold stage and analysed by the DFT as detailed in Wheeler et al (2015). The droplets were cooled at a constant rate of 5 • C min −1 from 0 to −35 • C. Each experiment was repeated three times using three different slides.…”
Section: Ice-nucleation Properties Of the Samples 221 Droplet Freezmentioning
confidence: 99%
“…For example, the IN activity of K-feldspar (Atkinson et al, 2013) may be altered by a change in composition of surface ions (Zolles et al, 2015). However, the lack of any effect upon heating samples to 60 • C suggests this was not the case (see also O'Sullivan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Mortierella alpina is a saprobe utilizing decaying organic matter (Wagner et al, 2013), and due to its ability to solubilize phosphorus also develops a mutualistic association with another fungal genus that forms mycorrhizal symbioses with sagebrush (Wicklow-Howard, 1994;Zhang et al, 2011). All 39 isolates tested by initiated freezing at −5 to −6 • C. They also typically released 10 8 to 10 9 small (< 10 nm) INPs per gram fresh weight of mycelium that nucleated between −5 and −8 • C (see O'Sullivan et al, 2015). For the three most common clades, which occurred in agricultural and lodgepole pine forest soils, digestion of isolates with papain lowered the INP concentration by ≈ 3-4 orders of magnitude , suggesting the INP was a protein.…”
Section: In Fungimentioning
confidence: 99%
“…Additionally, no correlation was found between freezing temperature and bacterial cell counts in the Arctic microlayer (Extended data Figure 4), which suggests that whole bacterial cells were not responsible for the observed ice nucleation. Given that terrestrial biological systems such as pollens 23,24 and fungi 25,26 have been found to produce nanoscale or 'macromolecular' INPs unconnected with whole cells, we considered the possibility that marine INPs are associated with exudates from phytoplankton or other marine microorganisms. This hypothesis is not only supported by the filtration tests, but by a tentative correlation between the North Pacific microlayer sample ice activation onsets with both the dissolved organic carbon concentration (DOC, >0.2 µm) and polysaccharide-rich transparent exopolymer particles (TEP) which are associated with phytoplankton exudates (Extended data Figure 5).…”
mentioning
confidence: 99%